2016
DOI: 10.1007/s00253-016-7616-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of technological properties of Enterococcus faecium CECT 8849, a strain isolated from human milk, for the dairy industry

Abstract: In this work, a variety of biochemical properties of Enterococcus faecium CECT 8849, which had been isolated from breast milk, were analyzed. Its acidifying capacity and proteolytic activity were low but, in contrast, remarkable peptidase and esterase activities were observed. Ethanol and 3-hydroxy-2-butanone were the most abundant volatile compounds found in experimental model cheese manufactured with E. faecium CECT 8849. This strain inhibited the growth of several Listeria monocytogenes and Listeria innocua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…The human milk microbiota may contribute to, at least, some of the functional properties and health benefits that epidemiological studies have associated with breastfeeding (Renfrew et al, 2012), including protection against infections, metabolic programming, immunomodulation and neuromodulation. Human milk bacteria may provide a certain degree of protection against infections caused by viruses, bacteria or fungi through a variety of mechanisms: (a) biosynthesis of compounds with antimicrobial activity, including organic acids (lactic acid, acetic acid, ethanol), bacteriocins, reuterin or hydrogen peroxide (Heikkilä and Saris, 2003;Beasley and Saris, 2004;Martıń et al, 2005;Martıń et al, 2006;Caŕdenas et al, 2016;Caŕdenas et al, 2019;Angelopoulou et al, 2020;Garcıá-Gutierrez et al, 2020); (b) coaggregation with pathobionts, impeding their access to the gut epithelial cells (Caŕdenas et al, 2019); (c) competitive exclusion with pathobionts for nutrients or host receptors (Olivares et al, 2006a;Martıń et al, 2010;Langa et al, 2012); (d) reinforcement of the infant gut barrier by preserving and decreasing intestinal permeability and increasing mucin biosynthesis (Olivares et al, 2006a;Vanhaecke et al, 2017;Liu et al, 2020); and (e) inmmunomodulation (Liu et al, 2020).…”
Section: Moving From Composition To Functionmentioning
confidence: 99%
“…The human milk microbiota may contribute to, at least, some of the functional properties and health benefits that epidemiological studies have associated with breastfeeding (Renfrew et al, 2012), including protection against infections, metabolic programming, immunomodulation and neuromodulation. Human milk bacteria may provide a certain degree of protection against infections caused by viruses, bacteria or fungi through a variety of mechanisms: (a) biosynthesis of compounds with antimicrobial activity, including organic acids (lactic acid, acetic acid, ethanol), bacteriocins, reuterin or hydrogen peroxide (Heikkilä and Saris, 2003;Beasley and Saris, 2004;Martıń et al, 2005;Martıń et al, 2006;Caŕdenas et al, 2016;Caŕdenas et al, 2019;Angelopoulou et al, 2020;Garcıá-Gutierrez et al, 2020); (b) coaggregation with pathobionts, impeding their access to the gut epithelial cells (Caŕdenas et al, 2019); (c) competitive exclusion with pathobionts for nutrients or host receptors (Olivares et al, 2006a;Martıń et al, 2010;Langa et al, 2012); (d) reinforcement of the infant gut barrier by preserving and decreasing intestinal permeability and increasing mucin biosynthesis (Olivares et al, 2006a;Vanhaecke et al, 2017;Liu et al, 2020); and (e) inmmunomodulation (Liu et al, 2020).…”
Section: Moving From Composition To Functionmentioning
confidence: 99%
“…The L-15 extract promoted chondrogenic differentiation by increasing certain extracellular matrix components (e.g., GAG). E. faecium is a type of LAB present in the human gastrointestinal tract and commonly used to produce fermented meat or dairy products [35,36]. Several groups have used LAB to induce adipogenic or osteogenic differentiation [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It was established that enterococci produce numerous volatile compounds and contribute to the formation of the cheese aroma, especially during ripening [17,91,100,138]. In the study of Cárdenas et al [139], a total of 41 volatile compounds were identified in experimental cheeses manufactured with E. faecium CECT 8849.…”
Section: Production Of Aromatic Compoundsmentioning
confidence: 99%